Odpowiedzi

Najlepsza Odpowiedź!
2009-12-15T14:16:03+01:00
X- tyle mam lat
y- tyle Ty masz lat
x>y
x+y=63
x=2 (y-(x-y))
x+y=63
x=4y-2x
x+y=63
3x=4y
x+y=63
x=4/3 y
4/3y+y=63
7/3y=63
y=63.3:7=27
x=27.4:3=36

Ja mam 36 lat
Ty masz 27 lat
xD
1 1 1
2009-12-15T14:17:16+01:00
X- tyle mam lat
y- tyle Ty masz lat
x>y
x+y=63
x=2 (y-(x-y))
x+y=63
x=4y-2x
x+y=63
3x=4y
x+y=63
x=4/3 y
4/3y+y=63
7/3y=63
y=63.3:7=27
x=27.4:3=36

Ja mam 36 lat
Ty masz 27 lat
2009-12-15T14:34:29+01:00
X - mój wiek
y - twój wiek

x+y=63
x=2*(y-(x-y))

x+y=63
x=2*(y-x+y)

x+y=63
x=2*(2y-x)

x+y=63
x=4y-2x

x+y=63
3x=4y/:3

x+y=63
x=4/3 y

4/3y+y=63
x=4/3 y

7/3y=63/:7/3
x=4/3 y

y=63:3/7=27
x=27:4/3=36

Ja mam 36 lat
Ty masz 27 lat